Reverse sweep: a story of South African cricket since apartheid: By Ashwin Desai. Auckland Park: Jacana Media, 2017 - Parry, Richard (Acta Academica: Critical views on society, culture and politics, 2018)
This passionate and perceptive book maps the politics of South African cricket from isolation through to transformation, in the light of competing political priorities. Ashwin Desai’s enthusiasm for the game itself and its players, and his commitment to political and economic change, shine clearly through this hard-hitting and sometimes controversial narrative.